Angular analysis of the decay B+ → K∗(892)+μ+μ− in proton-proton collisions at √s = 8 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Bergauer T. Thomas; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2021, 2021)
Title screen